Optimasi Pembuatan Daging Tiruan Umbi Porang (Amorphophallus oncophyllus) dan Isolat Protein Kedelai dengan Metode RSM (Response Surface Methodology) - Triana Lindriati; Ahmad Nafi; Zelika Gita Sari (Agricultural Faculty, 2019)
Meat analogue is a form of product which has originated from vegetal component which has a lot of tissue and could replace animal meat. The forming of meat analogue is using the extrusion technique. Primary ingredient which used is isolate soy protein and water, but also it is able to be added by other carbohydrates source such as porang bulb (Amorphophallus oncophyllus) wherewith increase the functional character over the meat analogue. This research is aimed for identify the optimum condition of proper treatment between the water additional formulation, isolate soy protein, porang bulb, therewithal the extrusion time. This reasearch was conducted in 5 phases: (1) determining the water content, isolate soy protein and porang bulb powder extrution time; (2) undertaking the randomization box-behnken model over RSM method. (3) Meat analogue forming based on the related randomization; (4) analysed parameters are; texture, WHC, OHC, protein solubility and organoleptic. The data analysis is using RSM Analyze. The optimization result of porang bulb meat analogue in the formulation of 90% water content, 18 minutes of extrusion time and 50% of used isolate soy protein. Meat analogue character with the optimization result as follows: texture 66,93 g/mm, WHC 304,98%, OHC 60,15%, protein solubility 80,06% and organoleptic 70,6%.